UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA 4-5 TAHUN MENGGUNAKAN KOTAK PENJUMLAHAN DI PAUD DIAULHAQ - Siti Nurhayati, Acih; Kania, Gina; Aminah, Siti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The learning of counting in early childhood should be designed using methods that are enjoyable, meaningful, and appropriate to the developmental stage of the children. Initial observations at PAUD Diaulhaq showed low counting skills, limited concrete media, and low interest in recognizing numbers. The use of concrete media, such as a counting box, is believed to help children understand number concepts, number order, and the concepts of bigger and smaller interactively. This study aims to improve the counting ability of children aged 4–5 years through the implementation of counting box media at PAUD Diaulhaq. This study used Classroom Action Research (CAR) with Kurt Lewin’s spiral model, which includes planning, action, observation, and reflection. The research subjects were 10 children in Group A (6 boys, 4 girls) aged 4–5 years. Data were collected through observation, interviews, and documentation, then analyzed descriptively both quantitatively and qualitatively. The results showed an improvement in children’s counting skills from pre-action to Cycle II. In the pre-action stage, the categories were Very Good (BSB) 0%, As Expected (BSH) 10%, Beginning to Develop (MB) 40%, Not Yet Developed (BB) 50%. In Cycle I, BSB 0%, BSH 20%, MB 50%, BB 30%. In Cycle II, there was significant improvement: BSB 30%, BSH 40%, MB 30%, BB 0%. Children were able to recognize numbers 1–10, understand number sequences, and distinguish bigger and smaller amounts interactively.